Workload-Based Pharmacy Staffing Needs Analysis Using WISN At Kimia Farma South Sumatra Pharmacy - Teguh Utama; Seftika sari; Satibi Satibi (International Journal of Health Engineering and Technology, 2026)
The availability of pharmaceutical personnel aligned with workload is essential for maintaining service quality, operational efficiency, and patient safety in retail pharmacies. This study aimed to analyze pharmaceutical staffing needs based on workload using the Workload Indicator of Staffing Needs (WISN) method in four Kimia Farma pharmacies in South Sumatra. A mixed-methods design was employed. Data were collected through focus group discussions, work sampling observations using a stopwatch, structured interviews, and secondary data, including patient visit reports and attendance records. Staffing requirements were calculated based on available working time, workload components, and allowance factors. The WISN ratios were 1.07458 at Sudirman Pharmacy, 1.16508 at Rosarum Pharmacy, 0.99705 at Symphoni Pharmacy, and 1.00414 at Rama Pharmacy. These findings indicate that staffing levels were generally adequate, although workload pressure varied across pharmacies. Support activities, particularly stock-taking, accounted for the largest proportion of working time and substantially influenced workload distribution. The findings demonstrate that staffing adequacy should be evaluated not only by workforce numbers or prescription volume but also by actual workload distribution. The WISN method provides an objective basis for pharmaceutical workforce planning and supports task redistribution, workflow simplification, enhanced administrative support, and improved information system utilization to optimize staffing efficiency in retail pharmacies.